Mekanisme Fundraising Dana Zakat, Infaq, dan Shadaqah Di Griya Derma Fakultas Ekonomi Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya - Ma’rifatuz Zakiah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2019)
Griya Derma ZISWAF Laboratory as an institution that manages zakat, infaq, shadaqah, and waqf cannot be separated from the name of Fundraising. So d need fundraising. Funding is an effort to collect, seek, and campaign to obtain funding in the form of money or outrage. This paper aims to find out: 1) Fundraising mechanisms for zakat, infaq and shadaqah funds at Griya Derma FEBI UIN Sunan Ampel Surabaya; 2) What are the weaknesses and advantages of zakat, infaq and Shadaqah fundraising at Griya Derma FEBI UIN Sunan Ampel Surabaya. The author uses interview techniques to obtain a number of data which is then analyzed the data. The findings in this paper include: 1) Fundraising Mechanism for Zakat Infaq Fund and Shadaqah The Amil Zakat Institution (LAZ) is a zakat management institution established by the community and confirmed by the government to collect, distribute and utilize zakat in accordance with religious provisions. Functions and roles, Griya Derma functions as an institution that manages zakat, Infaq and shadaqah (ZIS) funds which aim to collect people's funds, and then distribute them to people in need. Griya Derma provides zakat collection services to donors with a variety of service options, one of which is through jungut officers (collectors). 2) Seeing the advantages that exist in Griya Derma which divides jungut based on the location of the donors so that no donors are missed, so funds can be collected maximally. This kind of zoning strategy can provide satisfaction to donors. So that all donors do not turn to other institutions. Because the Fundraising Division uses the services of jungut which every month takes donations directly to lecturers, students, and the general public. Fundraising is a proactive and convincing activity, imagination and creativity, as well as friendship and trust. Fundraising activities are very important for social institutions or organizations to carry out activities carried out by these social institutions or organizations.